2020
DOI: 10.3390/nano10030508
|View full text |Cite
|
Sign up to set email alerts
|

Highly Rectifying Heterojunctions Formed by Annealed ZnO Nanorods on GaN Substrates

Abstract: We study the effect of thermal annealing on the electrical properties of the nanoscale p-n heterojunctions based on single n-type ZnO nanorods on p-type GaN substrates. The ZnO nanorods are prepared by chemical bath deposition on both plain GaN substrates and on the substrates locally patterned by focused ion beam lithography. Electrical properties of single nanorod heterojunctions are measured with a nanoprobe in the vacuum chamber of a scanning electron microscope. The focused ion beam lithography provides a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…Thin silver wire, glued by conductive silver paste, provided the ohmic contact to the silicon substrate. The bias voltage was applied between the needle and the grounded substrate [44,45]. The current-voltage characteristics were measured for the two different types of nanowires with different shapes and polarities.…”
Section: Ebic and Nano-probe Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thin silver wire, glued by conductive silver paste, provided the ohmic contact to the silicon substrate. The bias voltage was applied between the needle and the grounded substrate [44,45]. The current-voltage characteristics were measured for the two different types of nanowires with different shapes and polarities.…”
Section: Ebic and Nano-probe Resultsmentioning
confidence: 99%
“…bias voltage was applied between the needle and the grounded substrate [44,45]. The current-voltage characteristics were measured for the two different types of nanowires with different shapes and polarities.…”
Section: Ebic and Nano-probe Resultsmentioning
confidence: 99%
“…In a recent study, a reduction in native defects at the surface is reported for ZnO nanoparticles annealed at various temperatures [15]. Similarly, significant improvements in ideality factor, rectification ratio, and reverse breakdown voltage are observed in ZnO/Si heterojunctions annealed in Nitrogen (N 2 ) atmosphere [10], [16]. Furthermore, better rectification is achieved for ZnO Schottky diode with seed layer pre-annealed in N 2 [17].…”
Section: Introductionmentioning
confidence: 88%
“…ZnO thin films (seed layers) can be patterned using a variety of techniques such as atomic layer deposition (ALD), 30 laser interference lithography, 31−33 self-assembly technology, 34 nanoimprinting, 35,36 ion beam etching, 37 and electron beam lithography (EBL). 38,39 The resist used in these methods mainly serves as a mask during the formation of the seed layer and growth of the NRs.…”
Section: Introductionmentioning
confidence: 99%
“…ZnO thin films (seed layers) can be patterned using a variety of techniques such as atomic layer deposition (ALD), laser interference lithography, self-assembly technology, nanoimprinting, , ion beam etching, and electron beam lithography (EBL). , The resist used in these methods mainly serves as a mask during the formation of the seed layer and growth of the NRs. , Urgessa et al used poly­(methyl methacrylate) (PMMA) resist as a mask to grow ZnO NRs in patterns created by EBL . NRs that are grown this way have a uniform morphology; however, the indirect growth mode has limited the NR density and increased the costs and complexity of the process.…”
Section: Introductionmentioning
confidence: 99%